Siyasi Coğrafya ve Etnocoğrafya Perspektifinden Filipinlerdeki Müslüman Topluluklar / Muslim Communities in the Philippines from the Perspective of Political Geography and Etnogeography - Atasoy, Emin (Journal of History Culture and Art Research, 2018)
ABSTRACT This article examined the historical development of the struggle of the Muslim communities concentrated in the Southern Philippines for cultural freedom and political independence. Additionally, this study also concentrated on, on the one hand, the attempts exerted to establish an Islamic state in the Southern Philippines and Christian-Muslim competition in the country, and on the other hand, the minority policies of the Philippine governments towards the Muslim communities. In the present article, both the historical background and political fate of both Filipino Muslims were discussed, and the ethnic, socio-cultural and demographic characteristics of this country were addressed. Besides, the issue of freedom of the people of Moro and the establishment problems of Muslim Mindanao Autonomous Region and Bangsamoro Autonomous Region were examined. It is the most important consequence of this work that the peace climate between the government forces and the Muslim guerrillas in the Southern Philippines, the continuation of the social, economic, political and cultural problems of the Moro people and the independence of the Muslim communities living in the Philippine islands. Provision of the peaceful climate between the government forces and the Muslim guerrillas in the southern Philippines, the continuation of social, economic, political and cultural problems of the Moro people, and the failure of the Muslim communities living on the Philippine islands to gain their independence were the most important results of this study. ÖZ Bu makalede Güney Filipinler’de yoğunlaşan Müslüman toplulukların kültürel özgürlük ve siyasi bağımsızlık mücadelesinin tarihsel gelişimi irdelenmiştir. Ayrıca bu çalışmada bir yandan Hristiyan-Müslüman rekabeti ile Güney Filipinlerde İslam devleti kurma girişimleri, diğer yandan da Filipinler hükümetlerinin Müslüman topluluklara yönelik azınlık politikaları büyüteç altına alınmıştır. Makalede hem Filipin Müslümanlarının tarihsel geçmişi ve siyasi kaderi tartışılmış, hem de bu ülkenin etnik, sosyo-kültürel ve demografik özellikleri ele alınmıştır. Ayrıca makalede Moro halkının özgürlük mücadelesi ile Müslüman Mindanao Özerk Bölgesi ve Bangsamoro Özerk Yönetim Bölgesinin kuruluş sorunlarına değinilmiştir. Güney Filipinlerde hükümet güçleri ile Müslüman gerillalar arasında barış ikliminin sağlanmış olması, Moro halkının sosyo-ekonomik, siyasi ve kültürel sorunlarının devam etmesi ve Filipin adalarında yaşayan Müslüman toplulukların bağımsızlıklarına kavuşamamış olmalarının tespit edilmesi bu çalışmanın en önemli sonuçlarıdır.